Chorus Wave Properties From Van Allen Probes: Quantifying the Impact of the Sheath Corrected Electric Field. Issue 7 (29th March 2023) - Hartley, D. P.; Christopher, I. W.; Kletzing, C. A.; Kurth, W. S.; Santolik, O.; Kolmasova, I.; Argall, M. R.; Ahmadi, N.
Abstract: A sheath impedance model has recently been developed to describe how the variable coupling impedance between the Van Allen Probes instrumentation and the ambient plasma affects both the amplitude and phase of electric field wave measurements. Here, the impact of this sheath correction on measured chorus wave properties, including electric field wave power and the Poynting vector, is directly quantified. It is found that the sheath‐corrected electric field wave power is typically between two and nine times larger than the uncorrected measurement, depending on wave frequency. The sheath correction typically increases the Poynting flux by a factor of ∼2, and causes the polar angle of the Poynting vector to switch hemisphere from parallel to anti‐parallel propagation in ∼2% of cases. The uncorrected data exhibit significant deviations from the theoretically predicted relationship between the wave vector and the Poynting vector whereas this relationship is well‐reproduced with the sheath‐corrected observations. Plain Language Summary: The wave electric field on Van Allen Probes has recently been corrected for sheath impedance effects, which can affect both the amplitude and phase of the measurements. Here, for the first time, we directly quantify the impact of this correction factor on chorus wave measurements of electric field wave power. We also investigate the impact on the Poynting vector direction and magnitude, which is itself determined from electric field observations and magnetic field measurements. It is found that after applying the sheath correction to chorus wave observations, the electric field wave power typically increases by a factor between two and nine, whereas the Poynting flux typically increases by a factor of ∼2. The relationship between the wave vector and the Poynting vector is compared to that expected from cold plasma theory, for both the corrected and uncorrected observations. Significant differences between observations and theory are apparent when using the uncorrected measurements, however the sheath‐corrected observations agree well with the theoretical predictions. Key Points: Sheath‐correction results in increase of electric field chorus wave power by a factor of 2–9, and increase in Poynting flux by factor of ∼2 Sheath correction causes the Poynting vector to switch hemispheres, from parallel to anti‐parallel propagation, in only ∼2% of cases Theoretically predicted relationship between wave vector and Poynting vector is well‐reproduced with sheath‐corrected data